INFORMATION TECHNOLOGY TERMINOLOGY IN CHAPTER XXXIII OF THE POLISH PENAL CODE OF 1997 - RADONIEWICZ, Filip (Comparative Legilinguistics, 2017)
In the introductory part of the article, the distinction between two frequently confused concepts - "data" and "information" was made and their definitions were given, to describe afterwards the basic classifications - "computer data" and "information system". For that purpose international legal statutes were recalled, including the OECD Guidelines for the Security of Information Systems of the 26th of November 1992 and the Council Framework Decision 2005/222/JHA of the 24th of February 2005 on attacks against information systems. In the main part of the article, the author focuses on the information concepts, which are used by the Polish legislator in the Chapter XXXIII of the Penal Code, in which computer crimes are enumerated. Attention is paid to inconsistency in terminology, conceptual overlaps between certain specifications, and lack of definition of the relevant concepts. As the conclusion it is stated that the measures so far undertaken by the legislator, to standardise the terminology, are inadequate. Therefore, further efforts regarding that issue are essential. What is more, introduction of definitions of the most relevant classifications - especially "information system" and "computer data" to the Penal Code is advisable.